1995
DOI: 10.1073/pnas.92.26.12105
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and comparative analysis of the human pre-T-cell receptor alpha-chain gene.

Abstract: In immature T cells the T-cell receptor (TCR) 18-chain gene is rearranged and expressed before the TCR a-chain gene. At this stage TCR 18 chain can form disulfide-linked heterodimers with the pre-T-cell receptor a chain (pTa). Using the recently isolated murine pTa cDNA as a probe, we have isolated the human pTa cDNA. The complete nucleotide sequence predicts a mature protein of 282 aa consisting of an extracellular immunoglobulin-like domain, a connecting peptide, a transmembrane region, and a long cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Recently, it has been shown that PDCs in the thymus 20 and human committed DC precursors that are present in adult peripheral blood and thymus 23,25 share with T-cell precursors the expression of pre-T␣ mRNA. 24 We extended these observations by showing that the PDC subset we isolated from leukemic patients expressed pre-T␣ transcript. The finding of a transcript associated with the T-cell differentiation pathway adds support to the putative lymphoid origin of the leukemic PDC subset we have analyzed.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, it has been shown that PDCs in the thymus 20 and human committed DC precursors that are present in adult peripheral blood and thymus 23,25 share with T-cell precursors the expression of pre-T␣ mRNA. 24 We extended these observations by showing that the PDC subset we isolated from leukemic patients expressed pre-T␣ transcript. The finding of a transcript associated with the T-cell differentiation pathway adds support to the putative lymphoid origin of the leukemic PDC subset we have analyzed.…”
Section: Discussionmentioning
confidence: 89%
“…This phenotypic analysis demonstrated that MDCs and PDCs were phenotypically different from the parental clone (Figure 2A). In addition, as previously described for normal PDCs, 20,[23][24][25] RT-PCR analysis revealed that PDCs isolated from leukemic patients expressed the lymphoid-associated transcript pre-T␣ ( Figure 2B). …”
Section: Imbalance Of Blood DC Subsets In Myeloid Leukemia Patientsmentioning
confidence: 99%
“…Because the thymus contains precursor cells capable of giving rise to DCs and to T, B, and NK cells (16,18,19), we investigated in purified thymic DCs the expression of lymphoid-related transcripts. Figure 6a shows that although the three DC subsets lacked CD3γ, CD19, RAG-1, and RAG-2 mRNA, pDCs expressed pre-Tα and λ-like 14.1 mRNA, that are T and B progenitor genes (37,38). Moreover, while searching for pDC specific markers (M.-C. Rissoan, unpublished data), we found a tag sequence corresponding to the Ets family transcription factor Spi-B (39) that has been described as exclusively expressed in lymphoid cells (40).…”
Section: Figurementioning
confidence: 99%
“…Moreover, pre-TCR does not require CD3␦ for its function (64). Unlike murine pre-T␣, human pre-T␣ has an endoplasmic reticulum retention signal in its cytoplasmic domain and is strongly associated with the CD3 chain (54,55). We detected abundant pre-T␣ RNA expression in all three T-ALL cell lines, yet surface pre-T␣ was barely detected, and only Molt3 showed increased intracellular pre-T␣ expression.…”
Section: Discussionmentioning
confidence: 75%
“…Pre-TCR signaling occurs through pathways reminiscent of signaling after TCR ligation in mature T cells based on knock-out and transgenic mouse studies (6, 31, 49 -53). However, critical differences exist between the mouse and human cytoplasmic domains of the pre-T␣ chain (5,25,54,55).…”
Section: Il-7r Expression and Pre-tcr Signaling In T-all Cell Lineskementioning
confidence: 99%